Investigating the Combined Effects of Fascial Distortion Model Manual Therapy and Balance-Strength Training in Individuals with Chronic Ankle Instability - Amin Mohammadi; Seyed Ehsan Sakhtemani; Lukas Trimmel; Krisztina Petricsevics; Alexandra Makai; Istvan Zsenak; Csaba Melczer; Péter Sándor Tardi (MDPI AG, 2024)
Background: The Fascial Distortion Model (FDM) is a relatively new manual therapy approach in the field of musculoskeletal physical therapy, and its potential effectiveness in treating chronic ankle instability (CAI) remains unexplored. Methods: A randomized controlled trial with 23 participants was conducted. Patients were randomly assigned to either the FDM + balance-strength training (BST) group (n = 8), receiving extra FDM sessions weekly in addition to two sessions of BST, or the BST group (n = 7). Healthy controls (n = 8) did not receive any treatment and participated only in pre- and post-test measurements. Objective measurements including Y-Balance Test Lower Quarter (YBT-LQ), Flamingo Balance Test (FBT), Weight-Bearing Lunge Test (WBLT), ankle joint range of motion (ROM), and Cumberland Ankle Instability Tool (CAIT) were recorded at baseline and the end of the intervention. The results demonstrated significant differences between the FDM + BST and BST groups for supination ROM (p = 0.008) and similarly for WBLT (p = 0.041), FBT (p = 0.40), YBT-LQ (p = 0.023), and CAIT score (p = 0.008). Moreover, while both groups demonstrated significant improvement at the post-test compared with their pre-test for plantarflexion and pronation ROM, WBLT, and CAIT score, the FDM + BST group demonstrated significant improvements in supination ROM, FBT, and YBT-LQ. Conclusion: Our study suggests that the addition of FDM concepts to a BST may lead to enhanced improvements in ankle ROM, static and dynamic balance, and self-reported outcomes in individuals with CAI compared to BST.